2021
DOI: 10.3389/fresc.2021.651688
|View full text |Cite
|
Sign up to set email alerts
|

An Online Physical Activity Intervention for Youth With Physical Disabilities: A Pilot Study

Abstract: Background: Physical activity (PA) interventions are limited in number and reach for youth with physical disabilities (YPD) who experience systemic barriers that may preclude their in-person participation. Further, a lack of theory in the development and evaluation of PA interventions impedes our understanding and replication of active components of behavior change. These limitations pose challenges in the effective promotion of PA in YPD. Theory-based and more inclusive methods of PA intervention delivery mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…When combining the low at-home activity guide adherence with the fact that the Zoom session activities focused more heavily on social, rather than physical, engagement it is possible that there was simply not enough motor skill and physical activity engagement for participants to improve their physical literacy and physical activity levels. While a recent study showed that online adapted programming was beneficial for physical activity promotion, there was also high program adherence by participants ( 20 ). The low program adherence seen in this study could have been a moderator in program efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When combining the low at-home activity guide adherence with the fact that the Zoom session activities focused more heavily on social, rather than physical, engagement it is possible that there was simply not enough motor skill and physical activity engagement for participants to improve their physical literacy and physical activity levels. While a recent study showed that online adapted programming was beneficial for physical activity promotion, there was also high program adherence by participants ( 20 ). The low program adherence seen in this study could have been a moderator in program efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, virtual physical activity programming for individuals with disabilities has been investigated. A pilot study conducted by Sharma and colleagues ( 20 ) focused on the outcomes of a virtual adapted physical activity program for youth with physical disabilities, with results indicating high program compliance, social cognitive benefits, and increased self-reported physical activity behaviours among participants. The use of online pre-recorded physical activity interventions for adults with intellectual disabilities was also found to be a feasible program option that presents benefits to physical activity participation and overall health for its participants ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation